Carl Van Vechten and the Harlem Renaissance : a portrait in black and white - Bernard, Emily, 1967- (Yale University Press, 2012)
"By the time of his death in 1964, Carl Van Vechten had been a far-sighted journalist, a best-selling novelist, a consummate host, an exhaustive archivist, a prescient photographer, and a Negrophile bar non. A white man with an abiding passion for blackness."-- Resumé vydavatele
Keywords: Van Vechten, Carl, -- 1880-1964; 19.-20. století; američtí spisovatelé -- 19.-20. století; Afroameričané v literatuře; Afroameričané; Harlemská renesance; American authors -- 19th-20th centuries; African Americans in literature; African Americans; Harlem Renaissance; biografie; monografie; elektronické knihy; biography; monographs; electronic books